The aroma of edible mushrooms - Sola, Juha (fi=Turun yliopisto|en=University of Turku|, 2017)
The literature part of this thesis describes the anatomy and detection skills of the sensory organ for the sense of smell. The used methods, differences in the human sensory properties and formation of the mushroom aroma are studied. The aim of this thesis was to identify and define which odorants are significant for the perceived orthonasal aroma of mushrooms. Gas chromatography-olfactometry (GC-O) and solid-phase micro extraction (SPME) coupled with gas chromatography-mass spectrometry (GC-MS) was used in the analysis to identify the aroma contributing odorants. Evaluators (n = 15, 10 women) for sensory evaluation were recruited and trained to sniff and to describe the perceived stimuli by smelling. Three training sessions were performed both with sniffing bottles in a sensory laboratory (ISO 8589) and by the GC-O instrument equipped with flame-ionization detector (FID). Odorants were characterized in four different Finnish mushroom species. Each mushroom was evaluated by 12 different evaluators in individual sessions. The descriptions of sensory attributes and their intensity were investigated. The detection threshold for important odorants was set at 50% detection frequency among the evaluators. The sensory evaluation showed that especially butanal, hexanal, methional, 1-octen-3-ol, 3-octanone and octanol contributed to the aroma of all four mushrooms. We were able to identify 35 volatiles and 24 volatiles were detected above the threshold from four different mushroom species. The study showed that GC-FID alone is not sufficient for aroma research. GC-O aromagrams (figures of sensory response to certain stimuli) did not correlate with GC-FID chromatograms, which indicates that mushrooms contain various aroma compounds that are present under the detection limit of used instruments.